C*-Algebras Generated by a System of Unilateral Weighted Shifts and Their Application - Beyaz Basak Koca; Nazim Sadik (Journal of Function Spaces and Applications)
We study the structure C∗-algebras generated by a system of unilateral weighted shifts. Finally the obtained results are applied to a class of integral equations.